Significance of Geo-Demographic Analysis for Targeted Marketing - Abhishek Shetty (North American Journal of Engineering Research, 2021)
This study provides a geo-demographic analysis at the postal ZIP code level for a leading brand in the home improvement sector in Texas. Using hierarchical cluster analysis, the research identifies the most appropriate ZIP code areas for targeted marketing campaigns aimed at increasing market share and customer retention. The analysis leverages marketing intelligence techniques to offer insights into customer segmentation and behavior, providing a foundation for data-driven marketing strategies.